THE INFLUENCE OF SOCIAL MEDIA ON ELECTION CAMPAIGNS AND THE LIMITS OF DIGITAL ADVERTISING - Naves, Ana Luisa de Oliveira; Cruz, AmandaVitória Silveira; Silva, Eloysa Alexandre Da; Marra , Giovanna Cavalcante; Marques, Izabela Cristina Mendes; Silva, Nathaly Christiny Andrade da; Seabra, Pedro Lucena; Oliveira, Robson Américo de; Silva, Laurentino Xavier da; Muniz, Aline de Assis Rodrigues do Amaral (CIPEEX, 2025)
Social media has been consolidating itself as one of the main tools for electoral campaigns, as it enables direct interaction with broad reach, low cost, and easy access. This dynamic contributes to an excessive volume of information, combined with the ease with which false content spreads, which can lead to misinformation, polarization, and voter control. This study aims to analyze the influence of social media on electoral campaigns and the legal limits of digital advertising. The methodology adopted is based on a bibliographic and documentary review, considering authors such as Recuero (2009) and Mendonça (2019), as well as electoral legislation, especially Law No. 9,504/1997 and Resolutions of the Superior Electoral Court (TSE). The results indicate that although digital platforms expand access to information and encourage political involvement, fake news in the media threatens the final outcome of elections, facilitating manipulations that compromise election transparency and informed voting. Therefore, the Superior Electoral Court (TSE) regulates the rules on digital electoral propaganda through specific resolutions for each election, detailing deadlines, contracting methods, prohibitions, and permissions, limiting the use of this tool in elections. Therefore, to ensure a fair electoral process, it is necessary to unite the articulation between laws, education, and digital collaboration. Protecting democracy depends on building a safer digital environment, ensuring that voters' decisions are based on information harmonious with democratic principles. Joint efforts are essential to safeguard elections and maintain democracy in the digital age.